The Value of Alarm Features in Identifying Organic Causes of Dyspepsia - Lone Galmstrup Madsen; Peter Bytzer (Canadian Journal of Gastroenterology, 2000)
The unaided clinical diagnosis of dyspepsia is of limited value in separating functional dyspepsia from clinically relevant organic causes of dyspepsia (gastric and esophageal malignancies, peptic ulcer disease and complicated esophagitis). The identification of one or more alarm features, such as weight loss, dysphagia, signs of gastrointestinal bleeding, an abdominal mass or age over 45 years may help identify patients with a higher risk of organic disease. This review summarizes the frequency of alarm symptoms in dyspeptic patients in different settings (such as the community, primary care and specialist clinics). The prevalence of alarm features in patients diagnosed with upper gastrointestinal malignancy or peptic ulcer disease is described. The probability of diagnosing clinically relevant upper gastrointestinal disease in patients presenting with alarm features and other risk factors is discussed. Alarm features such as age, significant weight loss, use of nonsteroidal anti-inflammatory drugs, signs of bleeding and dysphagia may help stratify dyspeptic patients and help optimize the use of endoscopy resources.